PELAKSANAAN PEMBELAJARAN KETERAMPILAN BED COVER DI PKBM SITI NURBAYA KOTA PADANG - Wiwid Zuryani (Universitas Negeri Padang, 2014)
The background of this research is the high participation of the residents in the program learn skills of